THE ROLE OF SERUM AND FOLLICULAR FLUID CYTOKINES IN SUCCESSFUL RESULTS OF IN VITRO FERTILIZATION PROCEDURE - Safarova, A.F. (World of Medicine and Biology, 2023)
The purpose of the study was to find out the association between cytokines of serum and follicular fluid and successful results of an in vitro fertilization procedure. A total of 131 patients were included in the study. They were grouped based on the outcome of the in vitro fertilization procedure. The cytokines in the serum and follicular aspiration fluid obtained during the process of oocyte pick-up were measured. There was no significant difference in cytokines levels in serum and follicular fluid in patients with and without success results of in vitro fertilization procedure. IL-1β (p=0.851), IL-6 (p=0.994) in follicular aspiration fluid and IL-1β (p=0.266), IL-5 (p=0.365) and IL-6 (p=0.377) were different in serum, but the differences were not statistically significant (p˃0.05). Our study suggests the nonsignificant association between some cytokines in serum and follicular fluid and successful results of in vitro fertilization procedure, but it is necessary to conduct the further studies for more detail results.
Keywords: pregnancy; reproductive technologies; immunological markers; female infertility